SUCCESSFUL DESENSITIZATION TO D-PENICILLAMINE IN A PATIENT WITH DRUG HYPERSENSITIVITY DURING TREATMENT FOR WILSON’S DISEASE (Vietnam Journal of Community Medicine, 2026)
Introduction: D-penicillamine is a chelating agent commonly used in the treatment of Wilson disease; however, it may cause delayed hypersensitivity reactions, typically occurring several weeks after initiation.Case presentation: A 14-year-old girl with Wilson disease developed a generalized morbilliform rash with pruritus after 7 days of D-penicillamine therapy. Patch testing performed 4 weeks later yielded a positive result, suggesting a delayed hypersensitivity reaction. Due to limited access to alternative agents such as trientine, a slow desensitization protocol to D-penicillamine was selected based on clinical experience, with corticosteroid premedication and antihistamines administered as needed. During desensitization, the patient experienced a mild rash that was well controlled. After 40 days, she successfully tolerated a therapeutic dose of 900 mg/day and continued outpatient treatment.Conclusion: This case suggests that patch testing may aid in the diagnosis of delayed hypersensitivity to D-penicillamine, and that slow desensitization may be a feasible option in settings where alternative therapies are not readily available; however, further studies are needed to evaluate its safety and efficacy.
Keywords: D-Penicillamine, Wilson’s disease, morbilliform rash, patch test, slow desensitization